2019
DOI: 10.29089/2019.19.00086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a novel herbal skin care ointment with regular ointments to treat skin around the abdominal stoma: A clinical trial study

Abstract: Introduction The incidence of gastric ulcers in patients with abdominal stoma is high and affects the quality of patients’ life. Aim To evaluate the effect of Adib herbal ointment containing chamomile rose, black nightshade origin versus Comfeel and Conveen ointments on the skin of abdominal stoma. Material and methods This is a clinical study in which the volunteers were stoma patients. Study group consisted of 52 qualified subjects, 26 were included in the experimental group and 26 in the control group. A 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…This study was in line with a study by Hajikarimi et al about the comparison of a novel herbal skin care ointment with regular ointments to treat skin ulcers around the abdominal stoma. the results of their study showed that although the rate of skin ulcers was not statistically significant between the two groups, the herbal ointment similar to regular ointments (Comfeel and Conveen ointments) could help heal skin ulcers around the stoma [12].…”
Section: Discussionmentioning
confidence: 94%
“…This study was in line with a study by Hajikarimi et al about the comparison of a novel herbal skin care ointment with regular ointments to treat skin ulcers around the abdominal stoma. the results of their study showed that although the rate of skin ulcers was not statistically significant between the two groups, the herbal ointment similar to regular ointments (Comfeel and Conveen ointments) could help heal skin ulcers around the stoma [12].…”
Section: Discussionmentioning
confidence: 94%